Influence of endodontic motors on the behaviour of root canal shaping instruments: an in vitro comparative study - Clémentine Reynette; Renaud Giess; Jeanne Davril; Jean-Marc Martrette; Éric Mortier; Rémy Balthazard; Marin Vincent (Nature Publishing Group, 2023)
Abstract Aims The endodontic literature reports a lot of comparative study on endodontic instruments, concerning as well their geometry, instrumental dynamics, material, mechanical behavior or heat treatment. However, to our knowledge, no study has focused on the influence of endodontic motors on the shaping abilities of endodontic instruments. Thus, the aim of this study was to analyze the influence of the endodontic motors on root canal shaping instruments. Method Dual Move (MICRO-MEGA, Besançon, France), Canal Pro CL2i (COLTENE, Alstätten, Suisse), Canal Pro Jeni Motor (COLTENE, Alstätten, Suisse), Ai Motor (WOODPECKER, Guilin, China), Wave One motor (VDW, Postfach, Munich) and Smart A (WOODPECKER, Guilin, China) were pre-clinically compared in continuous rotation and reciprocating motion on a traction/compression bench using resin blocks. Canal shaping in continuous rotation and reciprocating motion were performed with One Curve and One RECI instruments (MICRO-MEGA, Besançon, France), respectively. The penetration/removal forces, making it possible to objectify the cutting effect and screwing effect of the instruments during root canal shaping, were analyzed. Results The results showed (i) that endodontic motors influence the mechanical behavior of endodontic instruments, (ii) that the influence of the motors is essentially felt during reciprocating motion and (iii) that the reciprocating angles influence the mechanical behavior of endodontic instruments. Conclusion Only endodontic instruments are widely studied in literature while endodontic motors have a direct influence on root canal treatment. This study analyzes the influence of the endodontic motors on root canal shaping instruments. This study tends to demonstrate that Jeni Motor could optimize the mechanical behavior of endodontic instruments.